LISTENING FROM THE BOTTOM A QUALITATIVE APPROACH EXAMINING ZAKAT RECIPIENTS’ VOICES - Zulkipli Lessy (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2013)
Existing zakat research, reports little information about the living conditions of Indonesian zakat recipients. This study examined the perceptions of zakat recipients at Rumah Zakat, a charitable institution, in Yogyakarta. Semi-structured interviews solicited seven economic empowerment program respondents’ narratives. This data collection method incorporating a phenomenological approach to data analysis revealed that respondents with more education and spousal support could better subsist after utilizing Rumah Zakat’s interest-free loans, and compared to individual efforts or group support, spousal support helped significantly with business growth. These respondents typically earned incomes above the national standard of poverty. As their businesses grew, four respondents planned to employ the jobless. Respondents benefiting from the program reported significant impact on their home economies and social lives.